MODEL PERTUMBUHAN TEGAKAN HUTAN ALAM BEKAS TEBANGAN DENGAN SISTEM TEBANG PILIH DI PAPUA - Relawan Kuswandi (Jurnal Pemuliaan Tanaman Hutan, 2017)
Sustainable forest management recently calls for growth information concerning integrated functions of ingrowth, upgrowth and mortality. This study was conducted in logging concessions of PT. Tunas Timber Lestari (TTL), PT. Wapoga Mutiara Timber (WMT) dan PT. Manokwari Mandiri Lestari (MML) in Papua. Then, this research was intended to build growth stands models in logged over forest. The data were obtained from permanent sample plots (PSPs) in three logging concession in Papua forest. Results revealed that characteristics of stand namely basal area, stem density and diameter had significant coefficients to model of ingrowth, upgrowth and mortality in each logging concession. Specifically, PT WMT showed the highest value of coefficient of determination (>80%, P<0.05). For PT MML only had significant model namely ingrowth and upgrowth model while PT TTL only shwed ingrowth model as significant equation.